Implementasi Good Local Governance di Kota Pangkalpinang pada Kepemimpinan Walikota Maulan Aklil - Ansyari, Irvan; Robing, Robing (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Good local governance is a form of government management at the local level that adheres to several principles, one of which is the principle of openness. Good regional governance is also the most prominent issue in the management of public administration today, especially regarding the shift in the role of bureaucrats from being people who want to be served to becoming an instrument of the state that must serve the people who already pay them through taxes. One of the principles of good local governance is the principle of accountability or responsibility, which means that the government as the manager of public administration is obliged to be responsible for their work towards the community, which must be carried out like consumers. Departing from the phenomenon that has occurred to date in Pangkal Pinang City, where during Maulan Aklil's leadership as Mayor he produced many achievements, including in the field of governance. One of the awards consistently received is that the Pangkal Pinang city government received the title of Unqualified Opinion (WTP) from the Financial Audit Agency. This means that Pangkal Pinang City has good financial performance accountability. The award indicates that the Pangkal Pinang City Government has succeeded in implementing one of the principles of Good Local Governance in managing governance and public administration, this of course cannot be separated from the leadership of Mayor Maulan Aklil in leading Pangkal Pinang City. This research aims to determine the implementation of Good Local Governance implemented by the Pangkal Pinang City Government, where Pangkal Pinang City consistently receives WTP awards. This makes this research important to carry out and it is hoped that it can later become a reference for other regions.